Evaluation of pigment composition and antioxidant properties in the flesh of seven colored pummelo cultivars - Peian Zhang; Quan Zhao; Yang Song; Huanchun Jin; Danelle Seymour; Yingyao Liu; Jun Chen; Dan Hu; Dongfeng Liu (Food Chemistry: X, 2025)
The color of pummelo fruit is an important trait, but specific pigments' contribution remains unclear. This study analyzed seven colored pummelo cultivars, including three red (Sanhongmiyou, Gusangyou, and Chuhongyou); three pale-red (Ruby pummelo, Guanximiyou, and Feihongyou) and one orange (Jinjumiyou). Carotenoid, flavonoid, and anthocyanin content and antioxidant capacity were analyzed for each cultivar. In the red and pale-red cultivars, narirutin and lycopene were the most abundant carotenoids and flavonoids, respectively, while β-carotene was the most abundant carotenoids in the orange cultivar. Anthocyanins were also detected in the three red cultivars, with the most abundant anthocyanin being cyanidin. Of the three red cultivars, Chuhongyou contained the highest levels of cyanidin (19.6 μg·g−1) compared to Sanhongmiyou (5.8 μg·g−1) and Gusangyou (2.8 μg·g−1. Polymethoxylated flavones, lycopene, and cyanidin-3-O-(6”-O-coumaryl)-galactoside were significantly correlated with antioxidant capacity. This study summarizes the pigment composition and antioxidant capacity in fruit flesh across a spectrum of pigmented pummelos.